2008
DOI: 10.1007/s10198-008-0121-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting chronic obstructive pulmonary disease (COPD)-related costs: a multivariate analysis of a Swedish COPD cohort

Abstract: Methods: A cohort of 179 subjects with COPD was interviewed over the telephone on four occasions about their annual use of COPD-related resources. The data set and the explanatory variables were analysed by means of multivariate regression techniques for six different types of cost: societal (or total), direct (health care) and indirect (productivity), and three subcomponents of direct costs -hospitalisation, outpatient, and medication.Results: Poor lung function, dyspnoea and asthma were independently associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
2
19
1
Order By: Relevance
“…An earlier study found signifi cantly higher hospitalization costs among patients with FEV 1 values <40% compared to patients with FEV 1 values >80% (28). As length of hospital stay is the main driver for hospitalization costs, this is comparable with our fi nding.…”
Section: Figuresupporting
confidence: 93%
“…An earlier study found signifi cantly higher hospitalization costs among patients with FEV 1 values <40% compared to patients with FEV 1 values >80% (28). As length of hospital stay is the main driver for hospitalization costs, this is comparable with our fi nding.…”
Section: Figuresupporting
confidence: 93%
“…productivity loss) were estimated in only two studies. Table 1 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] summarizes the details of the selected articles.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, age groups 80-85 and more than 85 years were found to determine a lower number of hospitalizations. Two studies did not report any positive association between age and costs [9,16]. In particular, Gerdtham et al [9] elaborated six different regression models to determine risk factors of both direct and indirect costs.…”
Section: ããmentioning
confidence: 97%
See 2 more Smart Citations